Excess mortality in solid organ transplant recipients hospitalized with COVID‐19: A large‐scale comparison of SOT recipients hospitalized with or without COVID‐19. Issue 1 (1st October 2021) - Jering, Karola S.; McGrath, Martina M.; Mc Causland, Finnian R.; Claggett, Brian; Cunningham, Jonathan W.; Solomon, Scott D.
Abstract: Background: Solid‐organ transplant (SOT) recipients with coronavirus disease 2019 (COVID‐19) have higher risk of adverse outcomes compared to the general population. Whether hospitalized SOT recipients with COVID‐19 are at higher risk of mortality than SOT recipients hospitalized for other causes, including non‐COVID‐19 pneumonia, remains unclear. Methods: We used logistic regression to compare outcomes of SOT recipients hospitalized with COVID‐19 to non‐COVID‐19 related admissions and with non‐COVID‐19 pneumonia. Results: Of 17, 012 hospitalized SOT recipients, 1682 had COVID‐19. Those with COVID‐19 had higher odds of ICU admission (adjusted odds ratio [aOR] 2.12 [95%CI: 1.88–2.39]) and mechanical ventilation (aOR 3.75 [95%CI: 3.24–4.33]). COVID‐19 was associated with higher odds of in‐hospital death, which was more pronounced earlier in the pandemic (aOR 9.74 [95%CI: 7.08–13.39] for April/May vs. aOR 7.08 [95%CI: 5.62–8.93] for June through November 2020; P ‐interaction = .03). Compared to SOT recipients hospitalized with non‐COVID‐19 pneumonia, odds of in‐hospital death were higher in SOT recipients with COVID‐19 (aOR 2.44 [95% CI: 1.90–3.13]), regardless of time of hospitalization ( P ‐interaction > .40). Conclusions: In this large cohort of SOT recipients, hospitalization with COVID‐19 was associated with higher odds of complications and in‐hospital mortality than non‐COVID‐19 related admissions, and 2.5‐fold higher odds of in‐hospital mortality, compared to SOT recipients with non‐COVID‐19 pneumonia.